IMPLEMENTATION OF MORAL VALUES IN EARLY CHILDHOOD IN THE FAMILY ENVIRONMENT IN RA BAAR, BARAT SAMBINASI VILLAGE, RIUNG DISTRICT NUSA TENGGARA TIMUR - Ilmia Luzu; Mila Oviani (Dirosatuna: Journal of Islamic Studies, 2021)
This research discusses the inculcation of moral values to early childhood at RA Baar East Nusa Tenggara. The background of this research listed as follows (1) Since the school has a vision and mission in installing good moral values among students (2) the uniqueness of the children in Ra Baar who demonstrate good morals (3) Major role of the family environment (parents) in instilling child's moral value. The type of research used is descriptive qualitative method. This research was conducted on one of the parents whose child possesses good morals both at school and family setting. Data collection techniques were carried out through 3 stages; observation, interviews and documentation. While the data analysis techniques are carried out through; data collection, data reduction, data presentation and drawing conclusions. The research output suggests that the process of inculcating children's moral values carried out by parents ​​around the family setting can be done by instilling religious faith in children, namely by introducing the phrase Laillaha Illallah to children, inviting children to regular worship, submitting the concept of both haram and halal, teaching good morals and appropriate manners, then by forming children's mentality, growing children's logical reasoning abilities, building children's social behaviours, giving children a sense of security and comfort, and increasing children's intelligence. Parents also provide encouragement and motivation to children so that they can value the implications of what has been instilled in children.